Adult family member experiences during an older loved one's delirium: a narrative literature review. Issue 11 (7th February 2015) - Day, Jenny; Higgins, Isabel
<x xml:space="preserve">Abstract</x> Aims and objectives To provide a narrative literature review about family experiences during older person delirium. Background Delirium is a common and serious condition which manifests when older people are unwell. Family members of older people are likely to encounter their loved one and become involved in care during delirium. Design Narrative literature review. Methods Electronic database and Google Scholar™ searches were conducted using search terms for delirium, family, experience and older people. Results Though family members are important partners in the care of older people, there has been little exploration of their experiences during delirium. Current literature identifies that family members experience unexpected, rapid and unpredictable changes in their older loved one, absence of the person they know, distress, not knowing about delirium nor how to help, and supportive and unsupportive relationships with health care staff. Conclusions Health care staff need understanding about what it means for family to have someone close to them have delirium. Without understanding, it is difficult for staff to respond with compassion, provide support and appropriately include family in the older person's care. There is a need to mitigate family distress and provide support, including information which addresses family concerns. Relevance to clinical practice The distress family members experience, the impact of losing connection to their loved one, and the difficulty family face in sustaining hope for their loved one's return needs to be recognised and addressed by health care staff, particularly nurses, during the older person's care.